2022
DOI: 10.6339/jds.201607_14(3).0010
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Financial Fraud Using Data Mining Techniques: A Decade Review from 2004 to 2015

Abstract: Objective: Financial fraud has been a big concern for many organizations across industries; billions of dollars are lost yearly because of this fraud. So businesses employ data mining techniques to address this continued and growing problem. This paper aims to review research studies conducted to detect financial fraud using data mining tools within one decade and communicate the current trends to academic scholars and industry practitioners. Method: Various combinations of keywords were used to identify the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(20 citation statements)
references
References 61 publications
(4 reference statements)
0
19
0
Order By: Relevance
“…In the initial stages, researchers mainly included Neural Network (NN), Linear regression (LR), Decision Tree (DT), Support Vector machine (SVM), Discriminant Analysis (DA) and Bayesian Belief Network. Supervised learning techniques were selected for analysis more than unsupervised ones, with 65% of the articles from US, China, Taiwan and Spain [10]. A considerable number of studies that analysed the performance of classifiers on FSF detection have shown that SVM [11,12,13,14,15], NN [16,17,18,19], DT [20,21] perform well in FSF detection/prediction.…”
Section: Related Researchmentioning
confidence: 99%
“…In the initial stages, researchers mainly included Neural Network (NN), Linear regression (LR), Decision Tree (DT), Support Vector machine (SVM), Discriminant Analysis (DA) and Bayesian Belief Network. Supervised learning techniques were selected for analysis more than unsupervised ones, with 65% of the articles from US, China, Taiwan and Spain [10]. A considerable number of studies that analysed the performance of classifiers on FSF detection have shown that SVM [11,12,13,14,15], NN [16,17,18,19], DT [20,21] perform well in FSF detection/prediction.…”
Section: Related Researchmentioning
confidence: 99%
“…During network training, it may appear that the input feature vector is too far away from the neuron, causing the neuron to never win the competition [21][22][23].…”
Section: Lvq Neural Network Algorithm Process Lvq Neuralmentioning
confidence: 99%
“…During network training, it may appear that the input feature vector is too far away from the neuron, causing the neuron to never win the competition [ 21 23 ]. The fraud identification process in accounting based on LVQ neural network is shown in Figure 3 .…”
Section: Lvq Neural Networkmentioning
confidence: 99%
“…e study applied a supervised learning strategy that used the classification technique. Supervised learning gives powerful capabilities for using machine language to classify and handle data [39].…”
Section: Design Of Studymentioning
confidence: 99%